Targeting non-coding RNA H19: A potential therapeutic approach in pulmonary diseases - Xie, Jinghui; Hu, Yuedi; Sun, Dengdi; Liu, Changan; Li, Zegeng; Zhu, Jie (Frontiers in Pharmacology, 2022)
Non-coding RNA is still one of the most popular fields in biology research. In recent years, people paid more attention to the roles of H19 in lung diseases, which expressed abnormally in various pathological process. Therefore, this review focus on the regulatory role of H19 in asthma, pulmonary arterial hypertension (PAH), idiopathic pulmonary fibrosis (IPF), lung injury, pneumonia, lung cancer, etc. And the potential therapeutic agents and molecular treatments of H19 are collected. The aim is to demonstrate its underlying mechanism in pulmonary diseases and to guide the basic research targeting H19 into clinical drug translation.